Design and Optimization Application of Cut Blasting Parameters for One-Time Completion of Blind Shaft - Yifeng Zhang; Yongsheng Jia; Nan Jiang; Quanming Xie; Lin Yuan; Yongbo Wu; Zehui Xu (Fractal and Fractional)
The one-time completion blasting technology for blind shafts is widely used in underground mining, for safety reasons. Efficient blind shaft excavation relies on reasonable cutting blasting technology. To optimize blasting parameters, the impact of explosion stress waves and gases on rock fragmentation is quantitatively analyzed using explosion stress wave theory. A calculation model for the radius R1 of the crushed zone and the radius R2 of the fractured zone in rock under the combined action of borehole cutting stress waves and blasting gases is derived and established. Combined with practical engineering examples and the determination method of compensation coefficient Cf, three types of linear cutting patterns, namely six-hole bucket cutting, seven-hole bucket cutting, and nine-hole bucket cutting, are designed. The post-blasting cavity volume and crack length of these three different cutting methods are calculated and analyzed using numerical simulation. Quantitative description of the distribution pattern of blasting-induced cracks in the simulation results of three cutting methods using the box-counting fractal dimension method are presented. Based on this analysis, the nine-hole bucket cutting is selected as the optimal scheme and validated through field application of cutting blasting. The results indicate that the nine-hole bucket cutting blasting scheme for one-time completion of blind shafts, with a designed hole depth of 8 m and a blasthole utilization rate of 93.7%, is an efficient and reasonable technical solution.